ANALISIS KAUSALITAS KREDIT EKSPOR LEMBAGA PEMBIAYAAN EKSPOR INDONESIA (LPEI), EKSPOR, DAN PERTUMBUHAN EKONOMI DI INDONESIA - Sumadiyasa, I Wayan Agus; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.02.TAHUN.2025DO - 10.24843/EEB.2025.v14.i02.p07, 2025)
This research aims to empirically analyse the causality between the real sector reflected by the value of exports, the monetary sector reflected by the export credit of Indonesian Eximbank (LPEI), and economic growth in seven regions of Indonesia. This study divides Indonesia into seven geographical sectors including DKI Jakarta, West Java, Central Java, East Java, Sumatra, Kalimantan, and Eastern Indonesia from 2011-2023, resulting in 91 observations. The data analysis technique uses the Panel Vector Error Correction Model (P-VECM). The results of this study indicate that export credit affects exports (unidirectional causality), exports and economic growth have a bidirectional causality, and export credit affect economic growth (unidirectional causality). The forecasting results show that the contribution of export credit, exports, and economic growth variables is dominantly derived from the variables themselves over the next 50 years. This research contributes practically for LPEI to increase export credit penetration for exporters outside Java Island, as well as for the government to diversify exports and equitable development of export-supporting infrastructure in seven regions of Indonesia.